The recursive definition of the sequence a
1. **Base Case**: To begin the recursion, we need to provide a starting point. Let’s define the first term:
- a1 = 1
This means that the first term in the sequence is 1.
2. **Recursive Step**: The next part of the definition involves creating the subsequent terms based on the previous term. According to the problem, for n > 1, we have:
- an = n * an-1 + 1
This means that each term a_n is obtained by multiplying the term’s index n by the previous term a_{n-1} and then adding 1.
3. **Summary of the Definition**: Combining both parts together, we have the full recursive definition:
- Base Case: a1 = 1
- Recursive Step: an = n * an-1 + 1 for n > 1
Using this recursive definition, we can generate terms in the sequence:
- a2 = 2 * a1 + 1 = 2 * 1 + 1 = 3
- a3 = 3 * a2 + 1 = 3 * 3 + 1 = 10
- a4 = 4 * a3 + 1 = 4 * 10 + 1 = 41
And so forth. Therefore, this recursive definition provides a systematic way to calculate the values of the sequence a